Molecular characterization of diarrheagenic Escherichia coli isolates from children with diarrhea - Manhique-Coutinho, Lena (2022)
Funding Information: The National Surveillance of Diarrhea was supported by a Senior Fellowship awarded to Nilsa de Deus by the European Foundations Initiative for African Research into Neglected Tropical Diseases (EFINTD, grant number 98539), the World Health Organization, a Master Fellowship funded by the Italian Agency for Development Cooperation (AICS) project AID10524, Deutsche Forschungsgemeinschaft (DFG, grant number JO369/5–1)—where Adilson Fernando Loforte Bauhofer and Assucênio Chissaque are fellows, GAVI (Global Alliance for Vaccines and Immunization) through Health System Strengthening (HSS), and Fundo Nacional de Investigação (FNI). The protocol was approved by the National Bioethics Committee for Health of Mozambique (IRB00002657, reference number: 348/CNBS/13), and each caregiver gave written informed consent to authorize their child's participation. The authors want to thank the parents or guardians who consented to their children's enrollment in the surveillance program. The authors acknowledge Dr. Octávio Jossai, the National Reference Laboratory of Microbiology team, all the focal points, and the provincial field teams who helped to conduct this study. Funding Information: The National Surveillance of Diarrhea was supported by a Senior Fellowship awarded to Nilsa de Deus by the European Foundations Initiative for African Research into Neglected Tropical Diseases (EFINTD, grant number 98539), the World Health Organization, a Master Fellowship funded by the Italian Agency for Development Cooperation (AICS) project AID10524, Deutsche Forschungsgemeinschaft (DFG, grant number JO369/5–1)—where Adilson Fernando Loforte Bauhofer and Assucênio Chissaque are fellows, GAVI (Global Alliance for Vaccines and Immunization) through Health System Strengthening (HSS), and Fundo Nacional de Investigação (FNI). Publisher Copyright: © 2022